IDENTIFIKASI KENDALA PADA PROSES PRODUKSI DENGAN MENGGUNAKAN THEORY OF CONSTRAIN (TOC) DALAM MENGOPTIMALKAN KAPASITAS PRODUKSI PDAM GUNUNG PANGILUN - Riko Ervil; Zela Novita Yulanda (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2020)
Padang Water Company, Gunung Pangilun Branch  is a provider of clean water for the community in the Padang city, especially the downtown part. In carrying out its duties, the Padang Water Company, Gunung Pangilun Branch has several problems that often occur. One of them is the high value of water loss that is in production, causing low value of water sales. This research uses the Theory Of Constrain (TOC) method used as a problem solving approach. TOC is used to identify constraints that become a constrain in the production process. In calculating the capacity used data sales forecasting water and after the calculation of capacity for each workstation there are 2 workstations that have a bottleneck, in  the Workstation 2 and Workstation 3. This makes the company need to focus on making repairs in two working stations that have a bottleneck.